The Wily Coyote - Smith; Bob (New York Sterling Publishers, 1997)
"The Wily Coyote" by Looney Tunes is a fun children's book centered around the iconic character Wile E. Coyote. In this story, Wile E. Coyote is on one of his classic and ambitious missions to catch the Road Runner. The book captures the comical and often disastrous attempts of Wile E. Coyote using various inventive, though ultimately unsuccessful, traps and schemes. Filled with slapstick humor and the signature antics of Wile E. Coyote, the story is designed to entertain young readers while showcasing the character's endless determination and the humorous consequences of his elaborate plans.